Aplikasi Penjualan Pulsa Elektronik Berbasis Android - Dwi Teguh Prasetyo; Nur Zahrati Janah; Supardianto Supardianto (Journal of Applied Informatics and Computing, 2017)
Nowadays, a mobile phone has transformed into a smartphone and not only used for communication. Further, then that, the mobile phone becomes a versatile item. You can use a mobile phone for browsing on the internet, you can pay something you buy using a mobile phone, you can order something you want via mobile phone, etc. everything gets easier because we can use mobile phone wherever and whenever we need. And to support the use of mobile phones, we need credit as a payment. Mobile credit transaction application for Android Devices is an application with user-friendly design and can make the credit’s seller easier to top up customer’s credit. This application can be used on an Android smartphone with minimal version android KitKat. The benefit of this application is to facilitate and accelerate the transaction credit delivery by the seller. This application is expected to facilitate the credit’s seller doing transaction by providing a transaction history, mark the customer’s debt and reports a valid seller's income as well as provide a report format the transaction automatically after the user do some settings at the beginning of the use of the application.